Innovative Tools and Methods for Education and Research on Modern Terrorism Studies - Rémai, Dániel (Magyar Rendészet, 2025)
The complex phenomenon of modern terrorism is constantly evolving, posing challenges not only to counterterrorism units and first response forces, but also researchers in the field and teachers of terrorism studies and counterterrorism. This paper will review the historical development of modern terrorism, global and regional trends, and the strategies and tactics of terrorist groups and individuals, counterterrorism strategies and responses to those changes. After a review of theoretical and historical background, we will focus on the challenges and opportunities in teaching theoretical knowledge about terrorism and counterterrorism methods. The presentation of the subject in higher education may differ in many respects from classical teaching methods and tools, and therefore case studies and best practices from home and abroad will be presented. Methods that promote interactive, experiential, cooperative and collaborative learning will be presented. The theoretical basis for this is the pedagogical school of problem-based learning and teaching. In addition to education, there is a clear need to provide an overview on the research of terrorism and its methodological issues and possibilities on that field, for example regarding innovative research tools, including big data analysis, network analysis and artificial intelligence, which allow for better understanding and potentially even the forecasting of terrorist activities. The aim of the study is to provide a comprehensive overview of the current state of terrorism in modern times and to present innovative approaches that can contribute to a better understanding of the phenomenon of terrorism.